DAYA TERIMA BROWNIES DENGAN SUBSTITUSI TEPUNG JEWAWUT (Setaria italica) - Manjilala Manjilala; Fatmawaty Suaib; Chaerunimah Chaerunimah; Sarnia Sarnia (Jurusan Gizi Poltekkes Kemenkes Makassar, 2021)
Anemia is a condition in which the circulating erythrocyte mass and hemoglobin mass do not fulfill their function to provide oxygen to body tissues. In Indonesia, the prevalence of anemia is 57.1% suffered by adolescent girls, 27.9% suffered by women of childbearing age (WUS) and 40.1% suffered by pregnant women. The main cause of nutritional anemia in Indonesia is the low intake of iron (Fe). Brownies with the addition of barley flour is an alternative to high-iron foods for people with anemia with unique creations and flavors, the appearance is also appetizing and does not leave the original characteristics of brownies which are rich in chocolate taste. This study aims to determine how the acceptability of brownies with the substitution of barley flour with concentrations of 5%, 10% and 15%. This research is a pre-experimental study, which was conducted at the Food Technology Laboratory, Department of Nutrition, Poltekkes, Ministry of Health, Makassar and its acceptance was carried out in Bau-Bau City. This study used 30 untrained panelists. Analysis of the data using the Friedman test and presented in the form of a table accompanied by an explanation in the form of a narrative.The results of the acceptability test from the aspect of color, texture and taste that are preferred are brownies with 5% barley flour substitution. while the preferred aroma aspect is brownies with 10% barley flour substitution. It is recommended that in making brownies a maximum of 10% barley flour is used so that the brownies can be accepted by consumers.